Can Leaders Enhance Follower Innovation by Requiring It?. Issue 1 (May 2016) - Craig, Jessica; Lopez, Patricia Denise
Abstract : Organizations today want to become more innovative, but should leaders include innovation as a job requirement for employees? While clear goals and roles enable accountability and results, innovation requires autonomy and risk‐taking amidst uncertain and unstable environments. The current article identifies the pros and cons of requiring innovation, and raises important questions for leaders to consider.